2004
DOI: 10.1182/blood-2003-11-4013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the chemokine receptor CCR2 on immature B cells negatively regulates their cytoskeletal rearrangement and migration

Abstract: In the bone marrow, B-cell development can be divided into different stages according to the rearrangement status of the immunoglobulin H (IgH) and IgL chain loci 1,2 and the expression of intracellular and surface-bound markers. The first cells expressing IgM at their surface during this developmental process are the immature B cells, 3 which leave the bone marrow and migrate to the spleen for their final maturation. 4,5 One of the most fundamental and important aspects of the immune system is its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…The chemokine receptor CCR2 is expressed on Ly6C hi monocytes and a subset of B cells, NK cells, NKT cells, pDC, and activated T cells (22)(23)(24)(25). However, following HSV-2 infection, the number of B cells, NKT cells, pDC, and activated T cells in the vaginal mucosa of CCR2 −/− mice were found to be comparable to that of WT mice (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The chemokine receptor CCR2 is expressed on Ly6C hi monocytes and a subset of B cells, NK cells, NKT cells, pDC, and activated T cells (22)(23)(24)(25). However, following HSV-2 infection, the number of B cells, NKT cells, pDC, and activated T cells in the vaginal mucosa of CCR2 −/− mice were found to be comparable to that of WT mice (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…CCR2 expression has been recently described on B cells and influences B cell functions [21,22]. To determine whether the altered autoantibody response in CCL2 -/-mice could be linked to CCR2 expression on B cells, we purified B cells from control mice and CCL2 -/-mice for studies of proliferation and production of antibodies.…”
Section: B Cell and Autoantibody Responses In Ccl2 -/-Micementioning
confidence: 99%
“…These 2 axes are both involved in the modulation of CXCL12-mediated chemotaxis. Indeed, it has been reported that the expression of CCR2 negatively regulates the cytoskeletal rearrangement and migration of immature B cells and that the control of Bcell homing by CCR2 is mediated by its ligand, CCL2, which is secreted by B cells and downregulates the CXCL12 signaling cascade (40)(41). On the contrary, a synergistic effect of CXCR4 and the EGFR on promoting cancer metastasis has been reported (45).…”
Section: Discussionmentioning
confidence: 96%
“…These 2 receptors that negatively regulate the CXCL12 signaling cascade in BCP cells (39)(40)(41) are both upregulated in Ba/F3 cells after ETV6-RUNX1 induction [MFI increase average of CXCR7: 16%, range: 6%-27%, P < 0.05 ( Supplementary Fig. S2B); fold change of the Ccr2 gene: 12.55, P < 0.01 ( Supplementary Fig.…”
Section: Etv6-runx1 Impairs Migration Toward Cxcl12mentioning
confidence: 99%